2017
DOI: 10.1007/s40843-017-9156-0
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline-phase-dependent catalytic performance of MnO2 for aerobic oxidation reactions

Abstract: Knowledge of the catalytic performances of different crystalline phases of a material is vital for the development of superior catalysts. In this study, different phases of MnO 2 (α, β, γ, and δ) have been prepared by the oxidation of Mn 2+, and their catalytic performances were evaluated using the aerobic oxidation of benzyl alcohol to benzaldehyde as a model reaction. α-MnO 2 promoted the reaction to the highest yield. However, when the yields were normalized by the corresponding surface areas, δ-MnO 2 exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It is well known that the benzyl alcohol thermal‐oxidation on MnO 2 ‐based catalysts follows the Mars–van Krevelen mechanism: benzyl alcohol is first oxidized by the surface lattice oxygen of the catalyst, and then oxygen vacancies generate on the surface of the catalysts, which are subsequently replenished by gas‐phase O 2 60–62 . Our group has demonstrated that cerium doping could improve the mobility of the surface lattice oxygen in the MnO 2 , thus accelerating the benzyl alcohol oxidation 41 .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…It is well known that the benzyl alcohol thermal‐oxidation on MnO 2 ‐based catalysts follows the Mars–van Krevelen mechanism: benzyl alcohol is first oxidized by the surface lattice oxygen of the catalyst, and then oxygen vacancies generate on the surface of the catalysts, which are subsequently replenished by gas‐phase O 2 60–62 . Our group has demonstrated that cerium doping could improve the mobility of the surface lattice oxygen in the MnO 2 , thus accelerating the benzyl alcohol oxidation 41 .…”
Section: Resultsmentioning
confidence: 86%
“…benzyl alcohol is first oxidized by the surface lattice oxygen of the catalyst, and then oxygen vacancies generate on the surface of the catalysts, which are subsequently replenished by gas-phase O 2 . [60][61][62] Our group has demonstrated that cerium doping could improve the mobility of the surface lattice oxygen in the MnO 2 , thus accelerating the benzyl alcohol oxidation. 41 In this work, the enhancement of benzaldehyde generation rates in bulk solution at the same temperatures was quite evident upon solar irradiation (Figure 4D), especially at high temperatures, indicating that the excellent catalytic performance of respectively.…”
Section: Photothermal Catalytic Performance Of the Ipc Reactormentioning
confidence: 99%
“…The MnO 2 nanocrystal is composed of a large amount of [MnO 6 ] octahedral units shared by the edges and corners, which gives rise to a variety of polymorphic forms, including α-type, δ-type, β-type, and γ-type. 26,27 It has been reported that the crystal phase of MnO 2 nanocrystal presented a significant influence on its catalytic performance. 28,29 To date, there are scarce reports about the application of MnO 2 as a heterogeneous catalyst for activating molecular oxygen in alkene epoxidation reactions.…”
Section: Introductionmentioning
confidence: 99%